2011
DOI: 10.1111/j.1473-2165.2010.00545.x
|View full text |Cite
|
Sign up to set email alerts
|

A succinct review of botulinum toxin in dermatology; update of cosmetic and noncosmetic use

Abstract: Botulinum toxin A has a wide variety of clinical applications in medical and dermatologic sciences. Nowadays, researchers introduce some other indications for botulinum toxin in cosmetic and especially noncosmetic aspects of dermatology such as medical rhinoplasty, hypertrophic scar, chemical brow lift, supraciliary wrinkles, pompholix, eccrine angiomatosis, Hailey-Hailey, dermatochalasis, lichen simplex, nosthalgia parestetica, and granulosis rubra nasi. In this general overview of the use of botulinum toxin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 62 publications
1
12
0
Order By: Relevance
“…Our study showed that triamcinolone acetonide used alone, or combined with BTA, provides similar clinical results in terms of scar improvement and symptomatic control. The results of our study confirmed the previous findings about the efficacy of triamcinolone on the keloids and some benefit of BTA on hypertrophic scars (Feily, Fallahi, Zandian, & Kalantar, ). Irradiation is mostly effective when administered in the adjuvant setting (i.e., after surgical excision) in which inhibitory effects on cell cycle and migration are optimized (Ramirez‐Fort et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…Our study showed that triamcinolone acetonide used alone, or combined with BTA, provides similar clinical results in terms of scar improvement and symptomatic control. The results of our study confirmed the previous findings about the efficacy of triamcinolone on the keloids and some benefit of BTA on hypertrophic scars (Feily, Fallahi, Zandian, & Kalantar, ). Irradiation is mostly effective when administered in the adjuvant setting (i.e., after surgical excision) in which inhibitory effects on cell cycle and migration are optimized (Ramirez‐Fort et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…BTA has a wide variety of clinical applications in medical and dermatological sciences . In recent years, BTA has also been reported as a treatment measure for hypertrophic scars .…”
Section: Discussionmentioning
confidence: 99%
“…19 In recent years, BTA has also been reported as a treatment measure for hypertrophic scars. 19,20 The molecular mechanism by which BTA promotes healing of hypertrophic scars is not yet perfectly explained, but BTA has been shown to inhibit proliferation and promote apoptosis of fibroblasts derived from hypertrophic scars. 21,22 In addition, BTA was reported to reduce the expression of transforming growth factor beta-1 (TGF-β1).…”
Section: Discussionmentioning
confidence: 99%
“…Of these, 26 underwent full-text review and 17 were excluded [ 6 , 10 25 ]. Among these excluded studies, three were conducted on animals [ 11 13 ], four were case reports [ 14 , 16 , 18 , 21 ], three were reviews [ 6 , 10 , 17 ], and another seven lacked raw data or contained useless data [ 15 , 19 20 , 22 25 ] ( S1 File ). Finally, nine articles met the inclusion criteria and were included in the analysis [ 1 , 26 33 ].…”
Section: Resultsmentioning
confidence: 99%